Hemostasis as a Total Physiological Function - Jaques, L. B (Thrombosis and Haemostasis, 1965)
The hemostasis is due to the combined action of several systems, blood composition, blood flow and vessels. The author reviews the factors which determine the vessel integrity and promote the repair after trauma.